The human eye and the sun : "hot" and "cold" light - Vavilov, S. I. (Sergei Ivanovich), 1891-1951 (Pergamon, 1965)
The Human Eye and the Sun, """"Hot"""" and """"Cold"""" Light is a translation from the Russian language and is a reproduction of texts from Volume IV of S.I. Vavilov, president of the U.S.S.R. Academy of Sciences. The book deals with theoretical and practical developments in lighting techniques. The text gives a brief introduction on the relationship of the human eye and the sun, describing the properties of light, of the sun, and of the human eye. The book describes hot (incandescence) and cold light (luminescence) as coming from different sources. These two types of light are compared. The.